Is Reverso A Good Translation Tool? Evidence from Translating Antonyms in Surat al-Raᵓd to English - Almommani, Shaimaa M. H.; Al Salem, Mohd Nour (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aims at evaluating the accuracy and acceptability of Reverso, a translation tool particularly used by Arabic-speaking university students who major in English, when translating religious texts from Arabic into English. Methods: To achieve the objectives of the study, the translations of the antonyms in Surat al-Raʕd (Thunder) as suggested by Reverso were located, studied and analyzed from a semantic perspective. These translations were checked against two translations of the Holy Quran, namely: Yosef Ali’s and Hilali-Khan’s. Ibn Kathir’s Exegesis in Arabic was also used to check the common meaning of the verses where the words appeared. In addition, two Arabic-Arabic dictionaries (Əlwɑsi:t and əlmɑʕæni:) and one English dictionary (Cambridge Online Free Dictionary) were consulted. Results: Reverso may work well in translating single words but fails in translating sentences that have antonyms. In addition, Reverso database lacks many religious terms, particularly those used in the Holy Quran. Conclusions: The study found that Reverso is not a guaranteed tool for translating religious texts. The findings of the study may be of value for translators who use this application in Islamic discourse.